Electrolytic preparation method of trivalent vanadium electrolyte
By combining oxalic acid chemical reduction and hydrogen discharge, and employing non-precious metal catalysts and controlling electrolysis parameters, the problems of high energy loss, high cost, and poor stability in the preparation of trivalent vanadium electrolyte in existing technologies have been solved, achieving efficient and low-cost preparation of trivalent vanadium electrolyte and improving battery performance.
Patent Information
- Application Number
- CN202511224394.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-09
AI Technical Summary
Existing technologies for preparing trivalent vanadium electrolytes suffer from problems such as high energy loss, high cost, unstable equipment operation, and corrosion, especially the use of precious metal catalysts and the low electrolysis efficiency caused by high voltage.
A method combining oxalic acid chemical reduction and hydrogen discharge was adopted. A non-precious metal catalyst was used to reduce the high-valence intermediate liquid to trivalent vanadium electrolyte under a stepped constant current. Electrolysis was carried out through a diaphragm stack, using carbon felt and porous media as electrodes, and controlling electrolysis parameters such as current density and voltage.
This method enables the preparation of trivalent vanadium electrolyte with low energy consumption and high efficiency, reducing costs, avoiding the use of precious metal catalysts, improving the reduction rate, preventing precipitate blockage, and enhancing electrolyte stability and battery performance.
Smart Images

Figure CN121097154A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of electrolyte preparation, and particularly relates to a method for preparing a trivalent vanadium electrolyte by electrolysis. BACKGROUND
[0002] The trivalent vanadium electrolyte is an important component of a full vanadium redox flow battery. In industrial production, the trivalent vanadium electrolyte is usually prepared by a chemical reduction-electrolysis method. In the method, V2O5 is first dissolved in sulfuric acid, and then a reducing agent is added to reduce the pentavalent vanadium to tetravalent vanadium, so as to obtain a tetravalent vanadium solution. Then, the tetravalent vanadium solution is further reduced by an electrolytic reduction process, and finally the trivalent vanadium electrolyte is obtained.
[0003] Currently, the electrolytic reduction process usually adopts two ways. First, the cathode chamber and the anode chamber adopt the same amount of tetravalent vanadium solution. As the charging electrolysis process proceeds, the reduction reaction occurs in the cathode chamber, and the tetravalent vanadium is reduced to trivalent vanadium to obtain the target solution. The oxidation reaction occurs in the anode chamber, and the tetravalent vanadium becomes pentavalent vanadium. This way has a high energy loss in the charging electrolysis, and the pentavalent vanadium in the anode chamber will precipitate in the form of a precipitate in the sulfuric acid system, which has the risk of pump blockage, causing the electrolysis process to be unable to continuously and stably proceed. The other way is to use dilute sulfuric acid as the anode in the electrolytic reduction process. As the charging electrolysis process proceeds, the reduction reaction occurs in the cathode chamber, and the tetravalent vanadium is reduced to trivalent vanadium to obtain the target solution. The oxidation reaction occurs in the anode chamber, and oxygen is generated by electrolysis. However, this electrolysis method needs platinum, ruthenium, iridium and other noble metals as catalysts, which increases the cost of the electrolysis process. In addition, the voltage required for electrolysis is too high, which easily corrodes the electrode plate, affects the electrolysis reaction, and has a low allowed current density, which prolongs the electrolysis time.
[0004] Therefore, there is an urgent need for an electrolytic reduction method for preparing the trivalent vanadium electrolyte, which has a low energy loss, a small influence on the operation of the device, and a fast reduction rate. SUMMARY
[0005] The application aims to provide a method for preparing a trivalent vanadium electrolyte by electrolysis.
[0006] As conceived above, the technical solution adopted by the application is as follows:
[0007] A method for preparing a trivalent vanadium electrolyte by electrolysis, comprising the following steps:
[0008] S1, mixing V2O5 and concentrated sulfuric acid to obtain a vanadium activation solution by stirring;
[0009] S2, adding oxalic acid to the vanadium activation solution to obtain a high-valence intermediate solution by chemical reduction;
[0010] S3, adding concentrated sulfuric acid in the same molar amount as V2O5 to the high-valence intermediate solution and stirring uniformly;
[0011] S4, using hydrogen as the negative electrode, using the solution in step S3 as the positive electrode electrolyte, and reducing the high-valence intermediate solution to a 3-valence vanadium electrolyte through stepwise constant current discharge.
[0012] Preferably, the molar ratio of V2O5 to concentrated sulfuric acid is 1:2.
[0013] Preferably, the concentration of sulfate ions in the vanadium activation solution is controlled to be 4-5.5 mol / L during preparation of the vanadium activation solution.
[0014] Preferably, the preparation of the vanadium activation solution is carried out under magnetic stirring at 500 rpm.
[0015] Preferably, the activation reaction temperature of the vanadium activation solution is 80-90°C, and the reaction duration is 3-5 h.
[0016] Preferably, the molar ratio of oxalic acid to V2O5 is 1:1.
[0017] Preferably, the temperature of the oxalic acid reduction reaction is 80-85°C, and the reaction time is 8-9 h.
[0018] Preferably, the molar concentration of vanadium in the high-valence intermediate solution is 1.5-2.2 mol / L.
[0019] Preferably, the concentrated sulfuric acid is added to the high-valence intermediate solution 3-5 h after the addition of oxalic acid.
[0020] Preferably, the molar ratio of the added concentrated sulfuric acid to V2O5 is 1:1.
[0021] Preferably, after the addition of sulfuric acid in step S3, magnetic stirring is carried out at 500 rpm, the temperature is 80-90°C, and the holding time is 3-5 h.
[0022] Preferably, in the electrolytic reduction process, the flow rate of hydrogen gas introduced is 10-15 mL / min.
[0023] Preferably, the current density of the stepwise constant current discharge is 300-500 mA / cm 2 and 150-250 mA / cm 2 , respectively.
[0024] Preferably, the cutoff voltage of the electrolysis process is 0-0.2 V.
[0025] Preferably, the electrolysis device uses a diaphragm-type cell, and the diaphragm is a perfluorosulfonic acid proton membrane.
[0026] Preferably, the electrolysis device uses carbon felt as anode and porous medium covered with catalyst as cathode.
[0027] Optionally, the electrolysis catalyst comprises platinum or non-noble metal, and the non-noble metal catalyst comprises at least one of molybdenum disulfide, tungsten disulfide, nickel phosphide, cobalt phosphide, iron phosphide and tricobalt tetroxide.
[0028] Optionally, the porous medium is selected from any one of carbon cloth, carbon fiber paper, porous ceramic material, graphite paper and metal mesh.
[0029] Preferably, before the preparation of the vanadium activation solution, V2O5 needs to be crushed and the particle size is controlled to be 100-200 mesh.
[0030] Preferably, the oxalic acid is analytical pure oxalic acid crystal with purity ≥ 99.5%.
[0031] Preferably, the hydrogen purity is ≥ 99.99%, and the hydrogen is dehydrated and purified before being introduced.
[0032] The present application has the following advantages:
[0033] 1. The present application adopts the discharge electrolysis mode, has less energy loss, is relatively more energy-saving, can use non-noble metal catalyst for the catalyst, reduces the cost, and does not need the same amount of high-valence electrolyte to match, which eliminates the hidden danger of 5-valence vanadium precipitating in the form of precipitate in the sulfuric acid system to block the pipeline.
[0034] 2. The discharge cutoff voltage of the present application is low, which reduces the possibility of corrosion of the electrode plate caused by excessively high voltage; and high current density can be used for electrolysis, which greatly accelerates the reduction reaction rate. BRIEF DESCRIPTION OF DRAWINGS
[0035] Figure 1 The figure is a schematic diagram of the device structure for preparing the 3-valence vanadium electrolyte of the present application.
[0036] Figure 2 The figure is a voltage and capacity curve of gradient electrolysis in the process of preparing the 3-valence vanadium electrolyte of the present application.
[0037] Figure 3 The figure is a comparison chart of the concentration of 3-valence vanadium ions after the high-valence intermediate solution electrolysis reduction of examples 1-7 and comparative examples 1-2 of the present application.
[0038] Figure 4 The figure is a comparison chart of energy efficiency and energy density of the battery assembled by using the 3-valence vanadium electrolyte prepared by example 1, comparative example 1 and comparative example 2 of the present application under a current density of 100 mA / cm 2 . DETAILED DESCRIPTION
[0039] The technical means, creative features, purposes and effects of the present application are described below in conjunction with specific embodiments.
[0040] As shown in Figures 1 to 4 , the present application comprises the following steps:
[0041] S1, mixing V2O5 with concentrated sulfuric acid and stirring to obtain a vanadium activation solution;
[0042] S2, adding oxalic acid to the vanadium activation solution for chemical reduction to obtain a high-valence intermediate solution;
[0043] S3, adding concentrated sulfuric acid in an equal molar amount to the high-valence intermediate solution and stirring uniformly;
[0044] S4, using hydrogen as the negative electrode, using the solution in step S3 as the positive electrode electrolyte, and reducing the high-valence intermediate solution to a 3-valence vanadium electrolyte by stepwise constant current discharge.
[0045] Example 1
[0046] V2O5 is placed in a sulfuric acid solution in a molar ratio of V2O5: concentrated sulfuric acid of 1:2, and a vanadium activation solution is obtained after activation at 85°C for 5h under magnetic stirring at 500rpm. Oxalic acid in an equal molar amount to V2O5 is added to the solution for reaction. Concentrated sulfuric acid in an equal molar amount to V2O5 is added to the above solution to make the reduction reaction more complete. The reaction is kept at 85°C for 3h under magnetic stirring at 500rpm, and the final ion concentration of the high-valence vanadium electrolyte is 1.5mol / L after the reaction is completed. As shown in Figure 1 , 25mL of the high-valence vanadium electrolyte is placed in the anode chamber of a battery. Platinum is used as the catalyst for the negative electrode, carbon fiber paper is used as the porous medium, and hydrogen is used as the negative electrode at a flow rate of 15mL / min. A stepwise discharge current density of 500mA / cm 2 , 250mA / cm 2 is used, and the discharge cutoff voltage is 0V. The 3-valence vanadium electrolyte is obtained after the reaction is completed. As shown in Figure 2 , the electrolysis curve of gradient electrolysis is stable, and the theoretical capacity is reached after the voltage cutoff. After the electrolysis is completed, the concentration of the 3-valence vanadium electrolyte is titrated, as shown in Figure 3 , the concentration of the 3-valence vanadium electrolyte reaches 1.492mol / L.
[0047] The 3-valence electrolyte obtained above is the negative electrolyte, and the positive electrolyte is the same volume of the high-valence intermediate solution.
[0048] The positive and negative electrolytes prepared in this example are applied to a flow battery. Carbon felt is used as the electrode, Nafion117 proton membrane is used as the separator, and the electrode projection area is 4cm 2.
[0049] The flow battery prepared in this example was tested under constant current density conditions, with 1.75 V and 0.8 V as the charge cut-off condition and discharge cut-off condition, respectively. As shown in Table 1, the energy density reached 20.6 Wh / L and the energy efficiency reached 84.1% after 30 cycles at a current density of 100 mA / cm 2 . Figure 4
[0050] Example 2
[0051] The rest are the same as Example 1, except that:
[0052] The negative electrode used molybdenum disulfide as a catalyst.
[0053] The flow battery prepared in this example was tested under constant current density conditions, with 1.75 V and 0.8 V as the charge cut-off condition and discharge cut-off condition, respectively. As shown in Table 1, the energy density reached 20.6 Wh / L and the energy efficiency reached 84.1% after 30 cycles at a current density of 100 mA / cm 2 .
[0054] Example 3
[0055] The rest are the same as Example 1, except that:
[0056] The negative electrode used tungsten disulfide as a catalyst.
[0057] Example 4
[0058] The rest are the same as Example 1, except that:
[0059] The flow rate of hydrogen gas was 12 mL / min.
[0060] Example 5
[0061] The rest are the same as Example 1, except that:
[0062] The flow rate of hydrogen gas was 10 mL / min.
[0063] Example 6
[0064] The rest are the same as Example 1, except that:
[0065] The electrolysis current density was 400 mA / cm 2 and 200 mA / cm 2 .
[0066] Example 7
[0067] The rest are the same as Example 1, except that:
[0068] Electrolysis current density is 300 mA / cm 2 and 150 mA / cm 2 .
[0069] Comparative Example 1
[0070] V2O5was placed in a sulfuric acid solution in a molar ratio of V2O5:H2SO4of 1:2, and a vanadium activation solution was obtained after activation at 85°C for 5h under magnetic stirring at 500 rpm. Oxalic acid was added to the solution in an equivalent molar amount to V2O5for reaction. Concentrated sulfuric acid was added to the above solution in an equivalent molar amount to V2O5to make the reduction reaction more complete, and the solution was kept at 85°C for 3h under magnetic stirring at 500 rpm. After the reaction was completed, the final ion concentration of the high-valence vanadium electrolyte was 1.5 mol / L. Equal volumes of 25 mL of the high-valence intermediate solution were independently placed in the positive and negative electrodes of the battery, and a stepwise charging current density of 500 mA / cm 2 , 250 mA / cm 2 was used, and the charging cutoff voltage was 2V. After the reaction was completed, the 3-valence vanadium electrolyte was obtained. After electrolysis, the concentration of the 3-valence vanadium electrolyte was titrated, and as shown in Table 1, the concentration of the 3-valence vanadium electrolyte reached 0.832 mol / L. Figure 3
[0071] The 3-valence electrolyte obtained above was the negative electrolyte, and the positive electrolyte was the same volume of high-valence intermediate solution.
[0072] The positive and negative electrolytes prepared in this example were applied to a flow battery, and carbon felt was used as the electrode, Nafion117 proton membrane was used as the separator, and the electrode projection area was 4 cm 2 .
[0073] The flow battery prepared in this comparative example was tested under constant current density conditions, and 1.75V and 0.8V were used as the charging cutoff condition and the discharging cutoff condition, respectively. As shown in Table 1, the energy density of 30 cycles at a current density of 100 mA / cm 2 was 12.3 Wh / L, and the energy efficiency was 62.1%.
[0074] Comparative Example 2
[0075] V2O5 is placed in sulfuric acid solution in a molar ratio of V2O5:H2SO4 of 1:2, and a vanadium activation solution is obtained after activation at 85°C for 5h under magnetic stirring at 500 rpm, oxalic acid is added to the solution in an equal molar amount as V2O5 for reaction; concentrated sulfuric acid in an equal molar amount as V2O5 is added to the above solution to make the reduction reaction more complete, and the reaction is kept at 85°C for 3h under magnetic stirring at 500 rpm, and the final ion concentration of the high-valence vanadium electrolyte is 1.5 mol / L after the reaction is completed and the volume is fixed; 25 mL of the high-valence vanadium electrolyte is placed in the cathode chamber of a battery, the anode plate is an iridium-plated titanium plate, the electrolyte is dilute sulfuric acid with the same concentration, and the charging current density is 500 mA / cm 2 , 250 mA / cm 2 in a stepwise manner, and the charging cutoff voltage is 2V, and the 3-valence vanadium electrolyte is obtained after the reaction is completed. Figure 3 As shown in the concentration titration of the 3-valence vanadium electrolyte after electrolysis, the concentration of the 3-valence vanadium electrolyte reaches 0.762 mol / L.
[0076] The 3-valence electrolyte obtained above is a negative electrolyte, and the positive electrolyte is the same volume of high-valence intermediate solution.
[0077] The positive and negative electrolytes prepared in this example are applied to a flow battery, carbon felt is used as the electrode, Nafion117 proton membrane is used as the separator, and the electrode projection area is 4 cm 2 .
[0078] The flow battery prepared in this comparative example is subjected to charge and discharge tests under a constant current density condition, and 1.75V and 0.8V are used as the charging cutoff condition and the discharging cutoff condition, respectively. As shown in Table 1, the energy density is 11.2 Wh / L and the energy efficiency is 57.6% under a current density of 100 mA / cm 2 after 30 cycles.
[0079] Comparative Example 3
[0080] The rest is the same as Comparative Example 1, except that:
[0081] The stepwise charging current density is 200 mA / cm 2 and 100 mA / cm 2 .
[0082] Comparative Example 4
[0083] The rest is the same as Comparative Example 2, except that:
[0084] The anode plate is an iridium-plated titanium plate, and the stepwise charging current density is 100 mA / cm 2 and 50 mA / cm 2 .
[0085] Comparative Example 5
[0086] Everything else is the same as Comparative Example 1, except that:
[0087] The stepped charging current density is 100mA / cm². 2 and 50mA / cm 2 .
[0088] Comparative Example 6
[0089] Everything else is the same as in Comparative Example 2, except that:
[0090] The stepped charging current density is 100mA / cm². 2 and 50mA / cm 2 .
[0091] Table 1 Comparison of Data from Examples and Comparative Cases
[0092]
[0093] As shown in Table 1, in this embodiment, there were no significant differences in the trivalent vanadium ion concentration, energy efficiency, and energy density between Examples 1-7, indicating that changing the hydrogen flow rate, catalyst type, and electrolysis current density within a certain range has little effect on the completeness of the electrolysis of the high-valent vanadium intermediate solution. Example 1 used platinum as a catalyst, a hydrogen flow rate of 15 mL / min, and 500 mA / cm². 2 250mA / cm 2 The discharge electrolysis current density reaches a trivalent vanadium ion concentration of 1.492 mol / L, an energy density of 20.6 Wh / L, and an energy efficiency of 84.1%, which is the optimal embodiment in the examples.
[0094] By comparing Example 1 with Comparative Examples 1 and 2, it was found that Example 1 can achieve electrolysis at high current density, while Comparative Examples 1 and 2 cause excessive polarization of the electrolysis system at high current density, leading to premature reaching of the cutoff voltage and termination before the reaction is complete. Figure 4 As shown, by comparing the vanadium redox flow battery in the comparative example and Example 1 at 100 mA / cm 2 The energy efficiency versus energy density curves after 30 cycles at the specified current density. In Comparative Examples 1 and 2, incomplete electrolysis and excessively low trivalent vanadium ion concentrations significantly impact the cycle performance of the assembled batteries, drastically reducing their energy density and energy efficiency.
[0095] By comparing between Example 1 and Comparative Examples 3-6, the reduction process of Example 1 is more complete, and Comparative Examples 3 and 5 have the phenomenon of blocking the pipeline in some cases due to the enrichment of pentavalent vanadium on the positive side in the case of too long electrolysis time. By comparing Example 1 with Comparative Examples 4 and 6, although the concentration of trivalent vanadium ions of Example 1 and Comparative Examples is similar in terms of electrolysis completeness, the stepwise charging current density of Example 1 is much higher than that of Comparative Examples 4 and 6, and therefore the electrolysis speed of Example 1 is much faster than that of Comparative Examples 4 and 6.
[0096] Specific principles:
[0097] As shown in Figure 1 , the redox potential of trivalent vanadium or tetravalent vanadium is 0.337 V vs. SHE, and hydrogen and the above-mentioned ions can constitute a primary cell. The positive electrode of the cell uses a certain amount of tetravalent vanadium solution, and the negative electrode uses hydrogen. With the progress of the discharging electrolysis process, the negative electrode undergoes an oxidation reaction, and hydrogen is oxidized to hydrogen ions. The positive electrode undergoes a reduction reaction, and tetravalent vanadium becomes trivalent vanadium, obtaining the target solution. The specific reaction principle in the discharging electrolysis process is as follows:
[0098] Positive electrode:
[0099] Negative electrode:
[0100] From the technical common sense, the present application can be realized by other embodiments without departing from the spirit or essential characteristics thereof. Therefore, the above-mentioned disclosed embodiments, in all aspects, are only illustrative, and not the only. All changes within the scope of the present application or within the scope equivalent to the present application are included in the present application.
Claims
1. A method for preparing trivalent vanadium electrolyte by electrolysis, characterized in that, Includes the following steps: S1. Mix V2O5 with concentrated sulfuric acid and stir until homogeneous to obtain vanadium activation solution; S2. Add oxalic acid to the vanadium activation solution for chemical reduction to obtain a high-valence intermediate solution; S3. Add concentrated sulfuric acid in an equal molar amount to V2O5 to the high-valence intermediate solution and stir until homogeneous; S4. Using hydrogen as the negative electrode and the solution from step S3 as the positive electrode electrolyte, the high-valence intermediate liquid is reduced to trivalent vanadium electrolyte through step-by-step constant current discharge.
2. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, In step S1, the molar ratio of V2O5 to concentrated sulfuric acid is 1:2, and the concentration of sulfate is 4-5.5 mol / L.
3. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, In step S1, V2O5 and concentrated sulfuric acid are kept at 80-90°C for 3-5 hours under magnetic stirring at 500 rpm to obtain vanadium activated solution after activation reaction.
4. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, In step S2, the molar ratio of oxalic acid to V2O5 is 1:1, the reduction reaction is carried out under magnetic stirring at 200-800 rpm, the temperature of the reduction reaction is 80-85℃, and the time of the reduction reaction is 8-9 hours.
5. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, In step S2, the molar concentration of vanadium in the high-valence intermediate solution is 1.5–2.2 mol / L.
6. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, In step S3, the molar ratio of concentrated sulfuric acid to V2O5 is 1:1, and the solution is kept at 80-90°C for 3-5 hours under magnetic stirring at 500 rpm.
7. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, In step S3, the concentrated sulfuric acid is added 3 to 5 hours after the addition of oxalic acid.
8. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, In step S4, the hydrogen gas is introduced at a flow rate of 10-15 mL / min and participates in the electrolysis process as the negative electrode.
9. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, In step S4, the current density of the stepped constant current discharge is 300–500 mA / cm². 2 150~250mA / cm 2 The cutoff voltage for stepped constant current discharge is 0 to 0.2V.
10. The method for preparing trivalent vanadium electrolyte by electrolysis according to claim 1, characterized in that, The electrolysis process requires platinum or a non-precious metal as a catalyst. The electrolysis device is a membrane stack, with carbon felt as the anode and a porous medium covering the catalyst as the cathode. The membrane of the electrolysis device is a perfluorosulfonic acid proton exchange membrane. The non-precious metal catalyst includes at least one of molybdenum disulfide, tungsten disulfide, nickel phosphide, iron phosphide, cobalt phosphide, and cobalt tetroxide. The porous medium includes any one of carbon cloth, carbon fiber paper, porous ceramic materials, graphite paper, and metal mesh.